Advanced materials for membrane-based gas separation - Ismail, A. F.; Kusworo, T. D.; Mustafa, A.; Hasbullah, H. (Penerbit UTM, 2006)
The development of advanced materials for membrane gas separation has received much attention in the recent years. There are many important aspects involved in the development of new and advanced membrane materials including the type of material, transport mechanism, the relationship between membrane structure and performance and membrane preparation techniques. There are numerous materials being widely investigated as suitable candidates using advanced materials for membrane gas separation. Therefore, this paper discusses the progress in the development of an advanced membrane material and methods to prepare membranes for gas separation. The recent development and future direction in membrane material research are also presented.